Improving Functional Capacity and Quality of Life in Parkinson’s Disease Patients through REAC Neuromodulation Treatments for Mood and Behavioral Disorders - Rinaldi, Chiara; Landre, Cleuton Braga; Volpe, Maria Izabel; Gonçalves, Rebeca Góes; Nunes, Lucas dos Santos; Darienso, Danyela; Cruz, Ana Vitoria; Oliveira, João Douglas; Rinaldi, Salvatore; Fontani, Vania; Barcessat, Ana Rita (Journal of personalized medicine, 2023)
Parkinson’s disease is a neurological disorder that affects both motor and non-motor functions, including depression, anxiety, and cognitive decline. Currently, it remains a challenge to distinguish the correlation between these aspects and their impact on one another. To try to clarify these reciprocal influences, in this study we have used specific radio electric asymmetric conveyer (REAC) technology neuromodulation treatments for behavioral mood disorders and adjustment disorders. In particular, we employed the neuro-postural optimization (NPO) and neuro-psycho-physical optimization (NPPOs) treatments. The study enrolled randomly 50 subjects of both genders previously diagnosed with Parkinson’s disease for at least six months. Prior to and following REAC NPO and NPPOs treatments, we assessed the subjects using functional dysmetria (FD) evaluation, five times sit to stand test (FTSST) for postural stability, and the 12-item Short-Form Health Survey (SF-12) for quality of life (QLF) evaluation. The positive results produced by the REAC NPO and NPPOs neuromodulation treatments, specific for mood and adaptation disorders, on dysfunctional motor disorders, and quality of life confirm how the non-motor components can condition the symptomatology of Parkinsonian motor symptoms. These results also highlight the usefulness of REAC NPO and NPPOs treatments in improving the overall quality of life of these patients.